Automatic Display Temperature Range Adjustment for Electrical Equipment Infrared Thermal Images. (December 2017) - Lin, Ying; Li, Chengqi; Yang, Yi; Qin, JiaFeng; Su, Xin; Zhang, Hao; Zhang, Weiwei
Abstract: With the important role in detecting electrical equipment defect, infrared thermography is widely used in power industries. With the rapidly increasing data of thermal images, the automatic processing for thermal images is more and more important. This paper presents a new approach to adjust the display temperature range of electrical equipment infrared thermal images. We first take advantage of the temperature distribution of thermal images to find two temperature peaks representing foreground and background respectively, and then find the new display temperature range according to the peaks. In the experiments, we collect 2000 images with improper display temperature ranges to validate the performance of our method. The experiment results show that our approach can effectively improve the image quality of thermal images, which helps the analysis of infrared thermal images.